Drug metabolizing enzymes in cancer therapeutics - Prasad, Bhagwat (Henry Stewart Talks, 2018)
Drug metabolism, Classification of drug metabolizing enzymes (DMEs), Clinical significance of DMEs in cancer therapeutics, Drug delivery, Drug resistance, Interindividual variability and precision oncology